Sintesis Membran Kitosan-Silika Abu Sekam Padi Untuk Penurunan Logam Berat Cu dengan Proses Ultrafiltrasi - Deasy Amanda Valentine; Sri Aprilia; Fauzi M Djuned (Jurnal Serambi Engineering, 2019)
This study chitosan membranes were made by phase inversion method by adding rice husk ash silica additives to the casting solution. This study aims to create and evaluate the characteristics of chitosan-silica rice husk ash membranes for application in reducing Cu heavy metals. Chitosan membrane modification is needed to produce membranes with better character, for example increasing membrane stability, reducing pore size so that the separation of molecules or rejection of macromolecules from a membrane solution is more effective. The concentration of chitosan-silica rice husk ash was varied at 20, 19, 17 and 15 (% by weight). The resulting membrane was further characterized for morphological structure parameters by scanning electron microscopy (SEM), fourier transform infrared (FTIR). Flux and solution rejection using dead-end filtration modules. The SEM test results show that the membrane has pores with asymmetric structures. Membrane performance test on Cu metal has a rejection value of 38%, 39%, 46% and 62% with flux gain reaching 0.4135 to 15.4377 L / hr.